C-FLIPR, a new regulator of death receptor-induced apoptosis - Golks, Alexander; Krammer, Peter H.; Lavrik, Inna N. (The journal of biological chemistry, 2005)
c-FLIPs (c-FLICE inhibitory proteins) play an essential role in regulation of death receptor-induced apoptosis. Multiple splice variants of c-FLIP have been described on the mRNA level; so far only two of them, c-FLIPL and c-FLIPS, had been found to be expressed at the protein level. In this report, we reveal the endogenous expression of a third isoform of c-FLIP. We demonstrate its presence in a number of T and B cell lines as well as in primary human T cells. We identified this isoform as c-FLIPR, a death effector domain-only splice variant previously identified on the mRNA level. Impor-/tantly, c-FLIPR is recruited to the CD95 (Fas/APO-1) death-inducing signaling complex upon CD95 stimulation. Several properties of c-FLIPR are similar to c-FLIPS: both isoforms have a short half-life, a similar pattern of expression during activation of primary human T cells, and are strongly induced in T cells upon CD3/CD28 costimulation. Taken together, our data demonstrate endogenous expression of c-FLIPR and similar roles of c-FLIPR and c-FLIPS isoforms in death receptor-mediated apoptosis.
Available online 4 January 2021
Elektronische Reproduktion der Druck-Ausgabe
Im Titel ist das "R" bei c-FLIP tiefgestellt
Gesehen am 04.03.2021